Digital transformation and the university library - Leiva-Aguilera, Javier (Anuario ThinkEPI, 2016)
The digital transformation of the university is linked to the integration of technology tools and digital resources to all areas of the organization: management, academic offerings, learning processes, research, and communication. This transformation is an obligation, but also an opportunity, not only to the university, but also to the its library, which can seize the opportunity to lead the process.